2015
DOI: 10.1097/ico.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Stress, Quality of Life, and Dry Eye Disease in Korean Women

Abstract: There is a close association between depression, stress, and DED in women who have been clinically diagnosed with it or those presenting with its symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 26 publications
4
87
1
4
Order By: Relevance
“…This indicates associations between dry eye symptoms, depression, and ADHD. In the present study, the DES group had a high depression score, and this is consistent with results of previous research [5,6,[8][9][10]. However, there has been no study on the association between DES and ADHD, but was attempted in the present study for the first time.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This indicates associations between dry eye symptoms, depression, and ADHD. In the present study, the DES group had a high depression score, and this is consistent with results of previous research [5,6,[8][9][10]. However, there has been no study on the association between DES and ADHD, but was attempted in the present study for the first time.…”
Section: Discussionsupporting
confidence: 82%
“…In a large-scale epidemiologic survey on 2,454,458 subjects relevant to Veterans Affairs, Galor et al [8] reported that 19% of the males and 22% of the females showed DES, and the risk factors of DES were post-traumatic stress disorder and depressive disorder. In a study on 6,655 adult females, Na et al [9] reported that the clinical diagnosis group was 12.3% and the symptom group was 20.0%, and the significant risk factors were severe psychological stress, depressive mood, anxiety/depression problems, and a history of psychological counseling. In a study on 248 ophthalmic patients who had visited the veterans Affairs Eye Clinic, Fernandez et al [10] reported that the groups with PTSD and depression had significantly higher Dry eye disease scores than the groups without PTSD and depression, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This result may also be caused by social factors, doctor visits and medical expenses. The depressive symptoms of eye disease patients deserve more attention4849.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies have shown the association of DED with depression, anxiety and stress 19,2325. In a study on elderly Koreans of age 65 years or older, Kim et al19 revealed that depression was related to dry eye symptoms in patients with normal or mildly reduced tear production.…”
Section: Association With Psychiatric Problemsmentioning
confidence: 99%
“…In a study on elderly Koreans of age 65 years or older, Kim et al19 revealed that depression was related to dry eye symptoms in patients with normal or mildly reduced tear production. In a large population-based study including 6,655 women of $19 years of age, Na et al25 revealed that subjects with DED showed increased risk of experiencing severe psychological stress, anxiety and depression. Yilmaz et al26 also reported that subjects with depression, stress and anxiety are more prone to DED.…”
Section: Association With Psychiatric Problemsmentioning
confidence: 99%